Effectiveness of Group Counseling Services with a Behavioristic Approach to Reduce Aggressive Behavior of High School Students in Bengkulu City - Hardianti, Susi; Jannah, Nurul (Corolla International Conference, 2025)
In this study, students' aggressive behavior was demonstrated verbally and nonverbally. The purpose of this study was to determine the level of aggressive behavior of students at SMA 4 Bengkulu City before and after receiving group counseling services. Is group counseling services effective in reducing the level of aggressive behavior of students at SMA 4 Bengkulu City? This study used a quantitative method, utilizing the guidance and counseling action research (PTBK) approach. Data collection tools used questionnaires and were analyzed using quantitative descriptive techniques, with a sample size of 11 students. The results of this study are: (1) Students' aggressive behavior before receiving group counseling services with a behavioristic approach was 64% very high and 36% high. (2) Students' aggressive behavior after receiving group counseling services with a behavioristic approach. At the end of the second cycle, the results were 9% moderate, 55% low, and 36% very low. (3) Based on the results of cycles I and II, it can be concluded that group counseling services with a behavioristic approach can reduce students' aggressive behavior.